Absent anti-N-methyl-D-aspartate receptor NR1a antibodies in herpes simplex virus encephalitis and varicella zoster virus infections. (1st February 2017) - Berger, Benjamin; Pytlik, Maximilian; Hottenrott, Tilman; Stich, Oliver
Abstract : Purpose : A 2012 report and subsequent case series described anti-N-methyl-D-aspartate receptor (NMDAR) antibodies in patients during the acute phase and relapse of herpes simplex virus 1 (HSV1) encephalitis (HSV1E). However, the prevalence of this phenomenon is unknown and systematic studies on other viral infections of the nervous system are missing. Materials and methods : We retrospectively analyzed serial cerebrospinal fluid (CSF) and serum samples of consecutive patients treated for neurological HSV1, HSV2 and varicella zoster virus (VZV) infections in our tertiary care university hospital between 2003 and 2013 for the presence of antibodies directed against the NR1a subunit of the NMDAR using indirect immunofluorescence. Results : In total, 88 patients with the following infections were identified through an electronic database search: HSV1 (24 with encephalitis), HSV2 (6 with meningitis, 3 with encephalitis and 1 with myelitis), or VZV (3 with meningitis, 33 with encephalitis, 17 with radiculitis and 1 with myelitis). Two patients with HSV1E and HSV2E, respectively, experienced a clinical relapse. Clinical follow-up was for up to 85 months, and repetitive serum and CSF analyses for up to 43 months. However, at no time did any of the 88 patients exhibit anti-NMDAR NR1a antibodies. Conclusions : In this study, we did not detect anti-NMDAR NR1a antibodies in serial CSF and serum samples of HSV1E patients or patients with other viral infections (HSV2 and VZV). However, the presence of antibodies directed against other epitopes of the NMDAR and other neuronal cell surface antigens cannot be excluded, necessitating further studies.